Southeast Asian Sharī‘ahs - Hooker, M.B. (Studia Islamika, 2013)
The Southeast Asian materials show that the sharī‘ah’s providing various pathways (through time and place) for individual Muslims to follow when doing their duty to God, which is fidelity to Revealed Truth. There are many paths and it is pointless to insist upon an historical ‘purist’ mono-legacy, however attractive this might appear theoretically. The realities of life (economics, social structure, alternative philosophies, and so on) dictate otherwise. Local sharī‘ahs adapt realities to Revelation irrespective of whether sources of legislation or forms of government are Muslim or non-Muslim this was never an issue in Southeast Asia. The localized sharī‘ahs were achieved via an acceptance of legal pluralism and hybridization of laws. The result is that Revealed obligations are phrased in local terms, change over time is allowed for, and the end result is a truly original and unique set of ‘Southeast Asian’ sharī‘ahs.DOI: 10.15408/sdi.v20i2.387